Evaluating the Histopathology of Pancreatic Ductal Adenocarcinoma by Intravoxel Incoherent Motion-Diffusion Weighted Imaging Comparing With Diffusion-Weighted Imaging - Liu, Qi; Zhang, Jinggang; Jiang, Man; Zhang, Yue; Chen, Tongbing; Zhang, Jilei; Li, Bei; Chen, Jie; Xing, Wei (Frontiers in Oncology, 2021)
Objectives: To explore the differences between intravoxel incoherent motion-diffusion weighted imaging (IVIM-DWI) and diffusion weighted imaging (DWI) in evaluation of the histopathological characters of PDAC. Methods: This retrospective study enrolled 50 patients with PDAC confirmed by pathology from December 2018 to May 2020. All patients underwent DWI and IVIM-DWI before operations. Patients were classified into low and high fibrosis group. Apparent diffusion coefficient (ADC), diffusion coefficient (D), false diffusion coefficient (D*), and perfusion fraction (f) were measured by two radiologists respectively. The tumor tissue was stained with sirius red, CD34, and CK19 in order to evaluate fibrosis, microvascular density (MVD), and tumor cell density. Furthermore, ADC, D, D*, and f values were compared with histopathological results. Results: The D values were lower in the high fibrosis group (1.26 ± 0.16 μm2/ms) than in the low fibrosis group (1.36 ± 0.18 μm2/ms) while the f values were opposite [(18.80 ± 4.98) % vs (13.03 ± 6.22) %]. Further, no statistically significant differences were found in ADC and D* values between the high and low fibrosis groups. The AUC of D and f values was 0.69 and 0.74, respectively, which had high evaluation efficacy in the high and low fibrosis groups. A significant negative correlation between D values and fibrosis (r = - 0.35, P = 0.01) and a significant positive correlation between f values and fibrosis were observed (r = 0.42, P = 0.01). Conclusions: D and f values derived from the IVIM model had high sensitivity and diagnostic performance for grading fibrosis in PDAC compared with the conventional DWI model. IVIM-DWI could serve as an imaging biomarker for predicting the fibrosis grade of PDAC.